Challenges around automotive shredder residue production and disposal. (March 2018) - Khodier, Ala; Williams, Karl; Dallison, Neil
Abstract: The challenge for the automotive industry is how to ensure they adopt the circular economy when it comes to the disposal of end-of-life vehicles (ELV). According to the European Commission the UK achieved a total reuse and recovery rate of 88%. This is short of the revised ELV directive target of 95% materials recovery, which requires a minimum of 85% of materials to be recycled or reused. A significant component of the recycling process is the production of automotive shredder residue (ASR). This is currently landfilled across Europe. The additional 10% could be met by processing ASR through either waste-to-energy facilities or Post shredder technology (PST) to recover materials. The UK auto and recycling sectors claimed there would need to be a massive investment by their members in both new capacity and new technology for PST to recover additional recycle materials. It has been shown that 50% of the ASR contains valuable recoverable materials which could be used to meet the Directive target. It is expected in the next 5 years that technological innovation in car design will change the composition from easily recoverable metal to difficult polymers. This change in composition will impact on the current drive to integrate the European Circular Economy Package. A positive factor is that main driver for using ASR is coming from the metals recycling industry itself. They are looking to develop the infrastructure for energy generation from ASR and subsequent material recovery. This is driven by the economics of the process rather than meeting the Directive targets. The study undertaken has identified potential pathways and barriers for commercial thermal treatment of ASR. The results of ASR characterisation were used to assess commercial plants from around the world. Whilst there were many claiming that processing of ASR was possible none have so far shown both the technological capability and economic justification.